(untitled) (Orthodontic Journal of Nepal, 2015)
Introduction: Bond strength is an important property and determines the amount of force delivered and treatment duration in orthodontics. Many light-cured bonding materials are being used; but it is required to determine the most efficient one with desired bond strength. Objective: To determine and compare the shear bond strength of three visible light-cured composites (Transbond XT, Heliositand Enlight) and two self-cured composites (Rely-a-bond and Concise). Materials & Method: 100 extracted premolars were collected and randomly divided into 5 test groups of different adhesives. Brackets were bonded to the teeth in each test group with the respective adhesive according to the manufacturer’s instructions. Each specimen was debonded using Universal Testing Machine and the shear bond strength for each specimen was calculated. All the groups were compared by ANOVA one-way test. Results: There were statistically significant differences among the five groups (P<0.05). The shear bond strength of Enlight (13.92 ± 3.92) is similar to Transbond XT (14.30 ± 4.35). Conclusion: Light cure composites showed higher bond strength than self cure composites.